Development of a questionnaire set to evaluate adaptations to COVID era: The ICS TURNOVER project (Transition of fUnctional uRology to New COVID ERa). Issue 2 (10th January 2022) - Hajebrahimi, Sakineh; López‐Fando, Luis; Arlandis, Salvador; Ghojazadeh, Morteza; Salehi‐Pourmehr, Hanieh; Hashim, Hashim
Abstract: Objectives: Coronavirus disease 2019 (COVID‐19) pandemic has caused a massive cutdown in outpatient urological investigations, procedures, and interventions. Female and functional urology (FFU) has been probably the most affected subspecialty in urology. Several scientific societies have published guidelines to manage this new situation, providing general recommendations. The aim of this study was to devise a robust questionnaire covering every different aspect of FFU to obtain recommendations on COVID‐19 adaptations. Methods: Delphi methodology was adapted to devise the survey questionnaires for male/female lower urinary tract symptoms (LUTS), pelvic organ prolapse (POP), chronic pelvic pain (CPP), and neuro‐urological disease. Content validity, face validity, and internal consistence were assessed to establish the final questionnaire. This study was ethically approved by the Local Research Ethics Committee. Results: A total 97, 59, 79, 85, and 84 items for female and male LUTS, POPs, CPP, and neuro‐urology respectively were approved by the participants. Content validity over 0.70 was obtained which seemed reasonable content validity scores. Internal consistency obtains values of Cronbach's alpha was between 0.70 and 0.90 which was acceptable. Conclusions: The collective wisdom obtained through a global survey using validated questionnaires covering every different aspect of FFU patient management is necessary. We have developed a robust and validated tool consisting of five questionnaires covering the most prevalent pathologies in FFU.